Paradigma Kritis Dalam Penelitian Wacana - Suharyo Suharyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
So far, linguistic research, especially discourse research, is still focused on aspects of the linguistic structure as forming the discourse. Discourse is examined for the existence of cohesiveness and coherence of the discourse. What are the linguistic units that form cohesiveness and cohesiveness both lexical and grammatical coherence. This is different from discourse research using critical discourse paradigms. Critical discourse holds that discourse-forming structures are not in a social